2020
DOI: 10.1186/s13362-020-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and multi-objective optimization to improve the final shape and process efficiency of a laser-based material accumulation process

Abstract: Common goals of modern production processes are precision and efficiency. Typically, they are conflicting and cannot be optimized at the same time. Multi-objective optimization methods are able to compute a set of good parameters, from which a decision maker can make a choice for practical situations. For complex processes, the use of physical experiments and/or extensive process simulations can be too costly or even unfeasible, so the use of surrogate models based on few simulations is a good alternative. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…By comparing Kriging and moving least square (MLS) method, it is found that the optimal results obtained by Kriging method are better than MLS method. Bansch et al [21] used meta-heuristic optimization model and finite element simulation for the complex process flow. The method can approximate the Pareto front through few finite element simulations.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing Kriging and moving least square (MLS) method, it is found that the optimal results obtained by Kriging method are better than MLS method. Bansch et al [21] used meta-heuristic optimization model and finite element simulation for the complex process flow. The method can approximate the Pareto front through few finite element simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The system under consideration couples a Navier-Stokes-like equation (1a) and (1b) with a Cahn-Hilliard system (1d) and an internal energy balance (1c). On the one hand, this system is interesting in terms of its applications, which reach from modeling of cancer evolution and treatment [26] over fluid flow for mixtures [4,7] and for instance modelling of industrial processes like 3d printing [8]. On the other hand, it serves as an interesting prototype of a thermodynamical consistent model of a complex fluid.…”
Section: Introductionmentioning
confidence: 99%